1723 Conn. Acts 292 - (:unkn) unknown (My University, 1723)
Prohibited the prosecution of "any Indian" for gun or ammunition except by a particular Court, requiring the guns be forfeited.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES